2005
DOI: 10.1074/jbc.m408308200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Carboxyl-terminal Tyrosines Modulates the Specificity of Sprouty-2 Inhibition of Different Signaling Pathways

Abstract: Sprouty proteins are evolutionarily conserved negative feedback regulators of multiple receptor tyrosine kinases. Mammalian versions of these proteins differentially regulate signaling induced by the fibroblast and the epidermal growth factors (FGF and EGF, respectively). Herein we show that, although both growth factors elevate expression of Sprouty-2, FGF-and not EGFinduced activation of the Erk/MAPK pathway is inhibited by Sprouty-2. Attenuation of FGF-signaling is accompanied by the induction of Sprouty-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…kinase Src was implicated in Spry2 tyrosine phosphorylation [Li et al, 2004]; however, other tyrosine kinases may also be involved [Rubin et al, 2005]. SIAH2 may serve as an additional mechanism to regulate Spry2 levels and decrease the inhibitory effects of Spry2 on MAPK signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…kinase Src was implicated in Spry2 tyrosine phosphorylation [Li et al, 2004]; however, other tyrosine kinases may also be involved [Rubin et al, 2005]. SIAH2 may serve as an additional mechanism to regulate Spry2 levels and decrease the inhibitory effects of Spry2 on MAPK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…4A). Furthermore, mutation of an additional tyrosine on the carboxy terminus, Y227F, which was shown to also affect the ability of Spry2 to attenuate FGF-induced MAPK activation [Rubin et al, 2005], was also degraded by SIAH2. The data presented here suggest that Spry1 and Spry2 protein levels may be regu- Fig.…”
Section: Siah2-mediated Degradation Of Spry2 Ismentioning
confidence: 99%
“…These dichotomous activities may in part reflect differences in the regulation of Sprouty2 by different growth factors as Sprouty2 inhibits Erk activity induced by fibroblast growth factor (FGF) and vascular endothelial growth factor, whereas augmenting signaling from EGF by increasing EGFR protein stability (46 -48, 53, 54). Tyrosine phosphorylation of Sprouty2 may contribute to these differences in the function of Sprouty2 as FGF but not EGF induces phosphorylation at Tyr-227 of Sprouty2, and this phosphorylation is required for inhibition of FGF-induced Erk signaling (55). MCF-10A cells are dependent on EGF for survival, proliferation, and growth factor signaling and express high levels of EGFR (7,56).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Spry1 is phosphorylated after FGF and platelet-derived growth factor stimulation, Spry2 is phosphorylated following EGF and FGF stimulation, whereas Spry4 is not phosphorylated following exposure to any of these growth factors. More recently, Rubin and co-workers (38) demonstrated that different tyrosine residues found in the C-terminal domain of Spry2 were phosphorylated in distinct patterns depending on the stimulus (either EGF or FGF), thus imparting a discriminatory role on this domain. Spry differences in function may also vary from cell to cell depending on which components of the RTK signalosome are present and activated by different ligands (3).…”
Section: Cooperative Inhibitorsmentioning
confidence: 99%